2023
DOI: 10.1161/circulationaha.123.064473
|View full text |Cite
|
Sign up to set email alerts
|

Defining Strategies of Modulation of Antiplatelet Therapy in Patients With Coronary Artery Disease: A Consensus Document from the Academic Research Consortium

Abstract: Antiplatelet therapy is the mainstay of pharmacologic treatment to prevent thrombotic or ischemic events in patients with coronary artery disease treated with percutaneous coronary intervention and those treated medically for an acute coronary syndrome. The use of antiplatelet therapy comes at the expense of an increased risk of bleeding complications. Defining the optimal intensity of platelet inhibition according to the clinical presentation of atherosclerotic cardiovascular disease and individual patient fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 56 publications
(27 citation statements)
references
References 53 publications
(108 reference statements)
0
27
0
Order By: Relevance
“…The experimental strategy examined herein represents one of several DAPT de-escalation approaches as articulated by the Academic Research Consortium. 30 Alternatives include switching from a more to less potent P2Y 12 inhibitor or reducing the dose of P2Y 12 inhibitor. With respect to the former, several studies have shown that switching from ticagrelor or prasugrel to clopidogrel after a minimum duration of DAPT, compared with not switching, reduces bleeding without compromising ischemic efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…The experimental strategy examined herein represents one of several DAPT de-escalation approaches as articulated by the Academic Research Consortium. 30 Alternatives include switching from a more to less potent P2Y 12 inhibitor or reducing the dose of P2Y 12 inhibitor. With respect to the former, several studies have shown that switching from ticagrelor or prasugrel to clopidogrel after a minimum duration of DAPT, compared with not switching, reduces bleeding without compromising ischemic efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Current guidelines recommend at least 12 months of dual antiplatelet therapy (DAPT), in the form of a combination of aspirin and a P2Y12 inhibitor, after implantation of a drug-eluting stent (DES) in patients with ACS, unless bleeding risks prevail. [3][4][5] However, maintaining long-term DAPT may be associated with excessive risk of bleeding. 5 Several randomized trials have evaluated de-escalation strategies for early stopping of aspirin to decrease bleeding events, [5][6][7][8][9][10][11][12] and recent meta-analyses from randomized trials have shown that eliminating aspirin after 1 to 3 months of treatment reduced the occurrence of bleeding events without increasing the number of ischemic events.…”
Section: Editorial See P 601mentioning
confidence: 99%
“…[3][4][5] However, maintaining long-term DAPT may be associated with excessive risk of bleeding. 5 Several randomized trials have evaluated de-escalation strategies for early stopping of aspirin to decrease bleeding events, [5][6][7][8][9][10][11][12] and recent meta-analyses from randomized trials have shown that eliminating aspirin after 1 to 3 months of treatment reduced the occurrence of bleeding events without increasing the number of ischemic events. [13][14][15] However, stopping aspirin within 1 month after implantation of a DES for ticagrelor monotherapy has not been exclusively evaluated for patients with ACS.…”
Section: Editorial See P 601mentioning
confidence: 99%
“…In this issue of Circulation , 3 papers contribute further to our knowledge in the context of contemporary clinical practice, 1–3 providing further insights into possible strategies for de-escalation of antiplatelet intensity. 4,5…”
mentioning
confidence: 99%